The Design and Implementation of the English Pronunciation Education Device - Kuo-Yi Chen; Wen Jie; Cai Cai (Faculty of Teacher Training and Education, Universitas Terbuka, 2019)
The English learning issue is always a problem for students who are not coming from native English countries. Among the problems of English learning, such as spelling, reading, writing, the most significant barrier could be English pronunciation. To improve this issue, we design and implement the English pronunciation education device. This device could help students to improve their English pronunciation with 3D printed blocks and real person voice.